2019
DOI: 10.1186/s12887-019-1511-x
|View full text |Cite
|
Sign up to set email alerts
|

Body mass index and dental caries in young people: a systematic review

Abstract: Background Obesity and caries in young people are issues of public health concern. Even though research into the relationship between the two conditions has been conducted for many years, to date the results remain equivocal. The aim of this paper was to determine the nature of the relationship between Body Mass Index (BMI) and caries in children and adolescents, by conducting a systematic review of the published literature. Methods A systematic search of studies examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
72
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(86 citation statements)
references
References 34 publications
8
72
0
6
Order By: Relevance
“…Previous literature reports that age influences the relationship between obesity and dental caries with the evidence of this relationship being stronger and consistent for older children (having permanent dentition) compared with young . The hypothesis is that both obesity and dental caries are slowly cumulative across the life course . However, present review found a positive association between the two conditions amongst children aged 6 years and younger having primary dentition, which highlights the need for early interventions to prevent these two health conditions.…”
Section: Discussionsupporting
confidence: 44%
See 4 more Smart Citations
“…Previous literature reports that age influences the relationship between obesity and dental caries with the evidence of this relationship being stronger and consistent for older children (having permanent dentition) compared with young . The hypothesis is that both obesity and dental caries are slowly cumulative across the life course . However, present review found a positive association between the two conditions amongst children aged 6 years and younger having primary dentition, which highlights the need for early interventions to prevent these two health conditions.…”
Section: Discussionsupporting
confidence: 44%
“…Based on the findings of this review, the recommendations for future research on this topic are presented below (many of which are consistent with previous systematic reviews): Use unified criteria for BMI categorisation and index for dental caries assessment. Use standardised overweight/obesity measurements, including trained and calibrated health professionals and related equipment and procedure. Use standardised measurements for dental caries assessment, including trained and calibrated dental examiners, and both clinical and radiographic assessment methods for better diagnostic accuracy. All the important potential confounding factors for association between overweight/obesity and dental caries should be adjusted in the data analysis using good study design practices. Longitudinal cohort studies with overweight/obesity as an “exposure” and dental caries experience as an “outcome” are needed to explore the potential relationship between overweight/obesity and dental caries in children aged 6 years and younger. Future studies investigating the complex relationship between the two conditions should employ good experimental study designs to assess the common risk factors (eg, diet, genetic, biomedical, and socio‐demographic) of overweight/obesity and dental caries using more systemic and universal measures. …”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations